Language use and attitudes as indicators of subjective vitality: The Iban of Sarawak, Malaysia - Ting, Su Hie; Tinggang, Andyson; Mertom, Lilly (2020)
The study examined the subjective ethnolinguistic vitality of an Iban community in Sarawak, Malaysia based on their language use and attitudes. A survey of 200 respondents in Song district was conducted. To determine the objective ethnolinguistic vitality, a structural analysis was performed on their sociolinguistic background. The results show the Iban language dominates in family, friendship, transactions, religious, employment, and education domains. The language use patterns show functional differentiation into the Iban language as the “low language” and Malay as the “high language”. The respondents have positive attitudes towards the Iban language. The dimensions of language attitudes that are strongly positive are use of the Iban language, Iban identity, and intergenerational transmission of the Iban language. The marginally positive dimensions are instrumental use of the Iban language, social status of Iban speakers, and prestige value of the Iban language. Inferential statistical tests show that language attitudes are influenced by education level. However, language attitudes and use of the Iban language are not significantly correlated. By viewing language use and attitudes from the perspective of ethnolinguistic vitality, this study has revealed that a numerically dominant group assumed to be safe from language shift has only medium vitality, based on both objective and subjective evaluation.